Cellulose-based dispersing agent, preparation method thereof and application of cellulose-based dispersing agent in preparation of large-size graphene

By using a mechanical peeling method using a cellulose-based dispersant, the problem of difficulty in preparing large-size graphene in the prior art is solved, and the preparation of large-size graphene with few defects and regular structures is achieved, with high stability and high yield.

CN119823291APending Publication Date: 2025-04-15ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510041354.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to produce defect-free, small-layer large-size graphene on a large scale, and the traditional methods have high cost and high safety risks, and it is difficult to control the size of graphene.

Method used

Large-sized graphene is prepared by mechanical peeling method using cellulose-based dispersant. The cellulose-based dispersant is produced by aldol condensation reaction, with high viscosity and π-π conjugation, helping to maintain the large size and structural regularity of graphite.

Benefits of technology

Large-size graphene with few defects and regular structures were achieved, with a lateral dimension of 50-300 μm and an average number of layers below 5 layers, with high stability, high solids content and high yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823291A_ABST
    Figure CN119823291A_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose-based dispersing agent, a preparation method of the cellulose-based dispersing agent and application of the cellulose-based dispersing agent in preparation of large-size graphene. The cellulose-based dispersing agent is an acetal compound generated by reaction of cellulose and aromatic aldehyde. Wherein the number-average molecular weight of the cellulose is greater than 8000. The large-size graphene is prepared by mixing the cellulose-based dispersing agent and the graphite liquid phase and then performing mechanical stripping, the process is easy to control, efficient and easy to operate, and the large-size, high-quality and high-yield graphene can be industrially produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of graphene preparation, and specifically relates to a cellulose-based dispersant and a preparation method thereof, as well as an application of the cellulose-based dispersant in the preparation of large-sized graphene. Background Art

[0002] Graphene is a single-layer two-dimensional carbon material with a honeycomb lattice structure and has an ultra-high electron mobility (200,000cm 2 / V·s), ultra-high thermal conductivity (5300W / mK) and ultra-high strength and other unique advantages have made it widely used in lithium batteries, heat dissipation, fibers, coatings and other fields. The lateral size is an important indicator of graphene, and its importance is second only to the thickness / number of layers of graphene. Generally speaking, according to the lateral size, graphene can be divided into: large-size / extra-large-size graphene, general-size graphene, small-size graphene, graphene quantum dots, etc. Among them, lateral dimensions greater than 50μm are called large-size graphene, and those greater than 100μm are called extra-large-size graphene. The thermal conductivity, electrical conductivity and mechanical properties of large-size graphene are much higher than those of small-size graphene. In addition, large-size graphene is more ideal in electronic devices due to its continuity and integrity. Therefore, the preparation of large-size graphene makes it possible to continuously improve the performance of the final product.

[0003] In the existing technology, the commonly used methods for preparing graphene include mechanical exfoliation, chemical vapor deposition, epitaxial growth, redox and electrochemical methods, but none of the above methods can produce large-scale defect-free, few-layer graphene. For example, large-scale preparation of large-scale graphene is currently mostly done by electrochemistry, or a combination of electrochemistry and redox, first obtaining graphene oxide and then further reducing it to obtain large-scale graphene. However, these methods not only have high process costs, but also have safety risks, and it is difficult to control the size of graphene during the exfoliation process. More importantly, the size of graphene obtained by these methods is mostly concentrated above 10μm, which is not a truly large-scale graphene. Although graphene prepared by mechanical exfoliation has the advantages of fewer defects, simple process and low cost, on the one hand, graphene with more than 10 layers is usually considered to be graphite microflakes, and simple mechanical exfoliation is more likely to obtain graphite microflakes rather than graphene; on the other hand, during the mechanical exfoliation process, due to the strong shear force and high-energy collision of external forces during the exfoliation process, the lateral size of the graphene is inevitably reduced rapidly, making it difficult to produce large-sized graphene.

[0004] Nevertheless, due to the simplicity of the mechanical exfoliation process and higher safety, it is still considered to be the most promising and effective method for cheaply and massively preparing high-quality large-sized graphene. However, there is currently no report on a method for preparing large-sized graphene using mechanical exfoliation. Summary of the invention

[0005] In view of this, the primary purpose of the present application is to provide a cellulose-based dispersant, which can be used for preparing large-sized graphene by mechanical exfoliation, which has the advantages of low cost, relatively simple and safe process control, and has high economic benefits and large-scale production value in industry.

[0006] In order to achieve the above objectives, this application adopts the following technical solutions:

[0007] One aspect of the present application provides a cellulose-based dispersant, which is an acetal compound generated by the reaction of cellulose and aromatic aldehyde; wherein the number average molecular weight of the cellulose is greater than 8000.

[0008] Another aspect of the present application provides a method for preparing the cellulose-based dispersant as described above, comprising the following steps:

[0009] The cellulose, aromatic aldehyde and water are fully mixed to form a uniform solution;

[0010] Then, an acid is added thereto, the temperature is raised for reaction, the pH of the system is adjusted to 7, an oxidant is added, and the mixture is dried to obtain the cellulose-based dispersant.

[0011] Another aspect of the present application provides the use of the cellulose-based dispersant as described above or the cellulose-based dispersant prepared by the preparation method described above in the preparation of large-sized graphene.

[0012] Another aspect of the present application provides a method for preparing large-size graphene, comprising the following steps:

[0013] After graphite, a cellulose-based dispersant and a solvent are uniformly mixed, they are mechanically exfoliated to obtain large-sized graphene; wherein the cellulose-based dispersant is as described above or is obtained by the preparation method described above.

[0014] Beneficial effects of this application:

[0015] (1) The present application introduces phenyl functional groups into cellulose through a functional group modification method to synthesize a cellulose-based dispersant. The aromatic rings in the cellulose-based dispersant easily form π-π conjugation with the graphene surface, and with the help of mechanical exfoliation, they are gradually intercalated into graphite, destroying the interlayer van der Waals forces, thereby preparing a few-layer graphene sheet with few defects and regular structure; on the other hand, the high molecular weight cellulose group increases the viscosity of the exfoliation system and weakens the impact energy of the external force during the mechanical exfoliation process, thereby maintaining the large size of the starting graphite during exfoliation, effectively avoiding the fragmentation of the graphite, and making the obtained graphene stably dispersed in the liquid phase, thereby obtaining a large-sized, high-stability, high-solid content, high-yield, and non-agglomerated aqueous graphene slurry, and a large-sized graphene powder can be obtained after conventional drying. The graphene obtained in the present application has a lateral size of 50 to 300 μm, which belongs to large-sized graphene, and the average number of layers is less than 5.

[0016] (2) The preparation reaction conditions of the cellulose-based dispersant in the present application are mild and easy to control, and the one-step preparation process is simple. A certain amount of aromatic rings can be introduced into the cellulose molecular chain through the aldol condensation reaction to synthesize the required cellulose-based dispersant. The prepared cellulose-based dispersant has a high stripping efficiency and is suitable for industrial production.

[0017] (3) In this application, a cellulose-based dispersant is used to mechanically exfoliate large-sized graphene. Compared with the traditional chemical preparation method, graphite can be mechanically exfoliated in the liquid phase, which simplifies the exfoliation process, is low-cost, and the process control is relatively simple and safe. The prepared graphene has the advantages of large size, few defects, few layers, and regular structure. It can not only be used directly in the form of slurry, but also can be dried to obtain powder. In addition, since the graphene surface is adsorbed with a cellulose-based dispersant, adding it to other polymer systems can obtain a highly uniformly dispersed graphene polymer composite material, which can be used in the fields of thermally conductive and electrically conductive functional coatings, thermally conductive plastics, thermally conductive rubbers, LED heat dissipation, transparent electrodes, capacitors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the principle of preparing large-sized graphene by mechanical exfoliation of cellulose-based dispersants in this application.

[0019] Figure 2 This is a synthetic route for the cellulose-based dispersant using hydroxyethyl cellulose as raw material in Example 1 of the present application.

[0020] Figure 3 This is the infrared spectrum of the cellulose-based dispersant prepared in Example 1 of the present application.

[0021] Figure 4 This is a scanning electron microscope image of the graphene prepared in Example 1 of the present application.

[0022] Figure 5 This is the laser Raman spectrum of the graphene prepared in Example 1 of the present application.

[0023] Figure 6 This is a transmission electron microscope image of the graphene prepared in Example 1 of the present application.

[0024] Figure 7 This is an optical photograph of the graphene powder prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0025] The following will clearly and completely describe the implementation methods of the present application. The technical solutions in the implementation methods described below are exemplary and are only possible technical implementations of the present application, not all possible implementations. Those skilled in the art can fully combine the implementation methods of the present application to obtain other implementation methods without creative work, and these implementation methods are also within the scope of protection of the present application.

[0026] The first aspect of the present application discloses a cellulose-based dispersant, wherein the cellulose-based dispersant is an acetal compound generated by the reaction of cellulose and aromatic aldehyde.

[0027] Cellulose is a polyhydroxy compound, and the hydroxyl groups on its surface can react with aromatic aldehydes to generate acetal compounds through aldol condensation reaction. Thanks to the advantages of cellulose and aromatic aldehydes, the prepared cellulose-based dispersant has functionalities such as water dispersibility, strong adsorption and anchoring functional groups for graphene, and impact cushioning effect brought by high viscosity, thereby being able to exert excellent mechanical exfoliation graphite effect.

[0028] In the present application, the cellulose is a type of polyhydroxy compound, and the number average molecular weight of the cellulose is greater than 8000; preferably, the number average molecular weight of the cellulose is greater than or equal to 25000. The high molecular weight of cellulose enables the prepared cellulose-based dispersant to increase the viscosity of the system during the mechanical exfoliation of graphite, thereby facilitating the maintenance of the large size of the original graphite and the preparation of large-sized graphene. In some specific embodiments of the present application, the number average molecular weight of the cellulose is 25000 to 30000.

[0029] In the present application, the type of cellulose is not particularly limited, and is preferably water-soluble cellulose. Specific examples include hydroxyethyl cellulose, methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, or a mixture of two or more thereof, but the invention is not limited thereto.

[0030] The aromatic aldehyde is an organic compound containing an aromatic ring and an aldehyde group (-CHO) in a class of structures, and the aromatic ring can be naphthalene or a benzene ring. In the present application, the aromatic aldehyde refers to an aldehyde containing at least one benzene ring in a molecular structure. The specific examples of the aromatic aldehyde include but are not limited to at least one of benzaldehyde, phenylacetaldehyde, phenylpropionaldehyde, and 2-naphthaldehyde. In some specific embodiments of the present application, in order to be more environmentally friendly, the aromatic aldehyde is preferably benzaldehyde.

[0031] The mechanical stripping principle of cellulose-based dispersants in this application can be seen in Figure 1 Among them, the hydroxyl groups in the cellulose molecular chain provide water solubility, and the introduced aromatic rings are easy to form π-π conjugation with the graphene surface. With the help of mechanical exfoliation, they are gradually intercalated into the graphite, destroying the interlayer van der Waals forces, thereby preparing a few-layer graphene sheet with few defects and regular structure; on the other hand, the high molecular weight cellulose-based dispersant increases the viscosity of the system, weakens the impact energy of external forces during mechanical exfoliation, avoids the fragmentation of graphite, and maintains the large size of graphite while efficiently exfoliating the graphite, so that the graphene is stably dispersed in the liquid phase, obtaining a large-size, high-quality, high-stability, high-solid content, high-yield, and non-agglomerated water-soluble graphene slurry, which can be subsequently dried conventionally to obtain large-size graphene powder.

[0032] The second aspect of the present application discloses a method for preparing the cellulose-based dispersant as described above, wherein the hydroxyl groups on the cellulose are subjected to an aldol condensation reaction with the aldehyde groups in the aromatic aldehyde to prepare the cellulose-based dispersant.

[0033] In some specific embodiments of the present application, the method for preparing the cellulose-based dispersant comprises the following steps:

[0034] The cellulose, aromatic aldehyde and water are fully mixed to form a uniform solution;

[0035] Then, an acid is added thereto, the temperature is raised for reaction, the pH of the system is adjusted to 7, an oxidant is added, and the mixture is dried to obtain the cellulose-based dispersant.

[0036] Among them, the ratio of cellulose, aromatic aldehyde and water can be determined by those skilled in the art through known methods or experiments, so there is no special limitation. In some specific implementation cases, the mass ratio of cellulose, aromatic aldehyde and water is 10: (0.1~1): (200~600).

[0037] In the reaction, the acid is used as a catalyst, which can be an organic acid or an inorganic acid, without special requirements. Specific examples include at least one of hydrochloric acid, nitric acid, sulfuric acid, and acetic acid. The concentration of the specific acid can be selected as required. In some specific embodiments of the present application, the mass concentration of the acid is 0.2% to 2%.

[0038] In the present application, the temperature of the aldol condensation reaction can be determined by those skilled in the art based on experience or experiments. They have such ability. In some specific embodiments of the present application, the temperature of the temperature-raising reaction is 40 to 100° C., and the reaction time is 2 to 10 hours.

[0039] In addition, after the reaction is completed, the system is adjusted to be neutral (pH=7), and a common alkali in the art (such as sodium hydroxide, potassium hydroxide, etc.) can be used to neutralize the acid in the reaction system to prevent the cellulose-based dispersant from degradation, so that it can be stored stably.

[0040] Furthermore, preferably, after the system is adjusted to be neutral, an oxidant (such as hydrogen peroxide) is added to the system to further oxidize the unreacted aromatic aldehyde in the system into aromatic acid, and finally filtered and dried to obtain the cellulose-based dispersant described in the present application.

[0041] In some specific embodiments of the present application, the added oxidant is hydrogen peroxide, and the added amount is twice that of the aromatic aldehyde.

[0042] The third aspect of the present application discloses the use of the cellulose-based dispersant as described above or the cellulose-based dispersant prepared by the preparation method described above in the preparation of large-sized graphene.

[0043] The fourth aspect of the present application discloses a method for preparing large-size graphene, comprising the following steps:

[0044] After graphite, the cellulose-based dispersant and the solvent are uniformly mixed, they are mechanically exfoliated to obtain large-sized graphene.

[0045] In the present application, there is no special requirement for the type and specification of graphite, and it can be a conventional type in the art. For example, the graphite can be natural flake graphite or expanded graphite, but it is not limited thereto. The size of the graphite can be 2 to 100 meshes.

[0046] In the present application, the solvent may be a common solvent used for mechanical exfoliation of graphite in the art, and specific examples include at least one of water, N-methylpyrrolidone (NMP), and N,N-dimethylformamide (DMF). In some specific embodiments of the present application, the solvent is preferably water, so that large-sized graphene is prepared by aqueous phase exfoliation. One reason is that the cellulose-based dispersant is water-soluble and can obtain a better exfoliation effect; the other reason is that the process has the advantage of being green and environmentally friendly.

[0047] In the present application, the ratio of graphite, cellulose-based dispersant and solvent is not particularly limited, and those skilled in the art can determine it through experiments, and they have such ability. In some specific embodiments of the present application, the mass ratio of graphite, cellulose-based dispersant and solvent is 20: (2-5): (75-78).

[0048] In the present application, the mechanical stripping can be carried out by a common method in the art, such as sanding. The specific process parameters of sanding can be adjusted according to actual needs. In some specific implementation cases, the sanding speed is 1000 to 3000 rpm, and the time is 5 to 25 hours.

[0049] It can be understood that in the present application, graphene slurry is obtained after mechanical exfoliation, and then large-sized graphene powder can be obtained through conventional drying. There is no special requirement for the drying method described here, for example, it can be any one of normal pressure drying, reduced pressure drying, spray drying, fluidized drying, freeze drying, etc.

[0050] The graphene prepared in the present application has a lateral size of 50 to 300 μm and an average number of layers of less than 5, and is high-quality, large-size graphene.

[0051] The following are specific embodiments of the present application. It should be noted that the following specific embodiments are only for illustrative purposes and do not limit the scope of the present application in any way.

[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0053] In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used are all commercially available.

[0054] Example 1

[0055] The present embodiment provides a preparation method of a cellulose-based dispersant and a method for preparing large-sized graphene by aqueous phase exfoliation of the cellulose-based dispersant.

[0056] 1. Preparation of cellulose-based dispersants

[0057] The specific process can be attended Figure 2 In a reactor, 10 g of hydroxyethyl cellulose (HEC) with a molecular weight of 25,000 to 30,000 and 1 g of benzaldehyde are dissolved in 200 g of water to form a uniform solution, and then 0.5 g of hydrochloric acid with a mass concentration of 2% is added. After the temperature is raised to 60°C, the reaction is carried out for 5 hours, and benzaldehyde and cellulose undergo an aldol condensation reaction to generate a product, cellulose condensation benzaldehyde; then sodium hydroxide is added to neutralize the acid in the system until the pH of the system is neutral, and then 2 g of hydrogen peroxide is added to further oxidize the benzaldehyde that has not participated in the reaction into benzoic acid to remove the bitter almond taste. After drying, a cellulose-based dispersant is obtained.

[0058] in, Figure 3 The infrared spectra of the cellulose-based dispersant and the raw material hydroxyethyl cellulose synthesized in this example are shown in Figure 1, where: 707 cm -1 and 764cm -1 The peak at 1453 cm is the out-of-plane bending vibration peak of the CH of the monosubstituted benzene ring. -1 and 1495cm -1 The peak at 3200cm is the skeleton vibration peak of the benzene ring, indicating that the cellulose-based dispersant contains benzene ring functional groups. -1 ~3600cm -1 There is a broad absorption peak in the range, which is the vibration absorption peak of OH, 2922cm -1 The peak at 3200cm is the CH absorption vibration peak of alkanes. -1 ~3600cm -1 The weakening of the absorption peak within the range indicates that hydroxyethyl cellulose participates in the reaction, proving that the cellulose-based dispersant is successfully prepared.

[0059] 2. Preparation of large-size graphene by aqueous phase exfoliation

[0060] 20 g of natural flake graphite (32 mesh), 2 g of a cellulose-based dispersant and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 10 hours to obtain a graphene slurry.

[0061] The graphene slurry is spray dried to obtain graphene powder ( Figure 7 ), according to the particle size analyzer test, the lateral size of the graphene powder is 70-120 μm, and the average number of layers is 5.

[0062] in, Figure 4 , Figure 5 and Figure 6 They are respectively a scanning electron microscope image (SEM), a Raman spectrum image and a transmission electron microscope image (TEM) of the graphene powder prepared in this embodiment. Figure 4 A wrinkled, transparent graphene sheet can be seen in the image. Figure 5 The Raman spectrum of graphene shows three characteristic peaks, D peak, G peak and 2D peak, indicating that the cellulose-based dispersant has a high efficiency in exfoliating graphite. Figure 6 The TEM image shows that the number of graphene layers prepared is small, about 5 layers.

[0063] The above characterization results all indicate that the cellulose-based dispersant prepared in this example has a highly efficient exfoliation effect on graphite, and large-sized, high-concentration, high-quality graphene can be obtained.

[0064] Example 2

[0065] The present embodiment provides a preparation method of a cellulose-based dispersant and a method for preparing large-sized graphene by aqueous phase exfoliation of the cellulose-based dispersant.

[0066] 1. Preparation of cellulose-based dispersants

[0067] Same as Example 1.

[0068] 2. Preparation of large-size graphene by aqueous phase exfoliation

[0069] 20 g of natural flake graphite (32 mesh), 2 g of a cellulose-based dispersant and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 12 hours to obtain a graphene slurry.

[0070] The graphene slurry is spray-dried to obtain graphene powder. According to a particle size analyzer test, the lateral size of the graphene powder is 60 to 90 μm, and the average number of layers is 4.

[0071] Example 3

[0072] The present embodiment provides a preparation method of a cellulose-based dispersant and a method for preparing large-sized graphene by aqueous phase exfoliation of the cellulose-based dispersant.

[0073] 1. Preparation of cellulose-based dispersants

[0074] In a reactor, 10 g of hydroxyethyl cellulose with a molecular weight of 25,000 to 30,000 and 1 g of benzaldehyde are dissolved in 600 g of water to form a uniform solution, and then 0.5 g of hydrochloric acid with a mass concentration of 2% is added. After the temperature is raised to 60°C, the reaction is carried out for 5 hours, and benzaldehyde and cellulose undergo an aldol condensation reaction to generate a product, cellulose condensation benzaldehyde; then sodium hydroxide is added to neutralize the acid in the system until the pH of the system is neutral, and then 2 g of hydrogen peroxide is added to further oxidize the benzaldehyde that has not participated in the reaction into benzoic acid to remove the bitter almond taste. After drying, a cellulose-based dispersant is obtained.

[0075] 2. Preparation of large-size graphene by aqueous phase exfoliation

[0076] 20 g of natural flake graphite (32 mesh), 2 g of a cellulose-based dispersant and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 15 hours to obtain a graphene slurry.

[0077] The graphene slurry is spray-dried to obtain graphene powder. According to a particle size analyzer test, the lateral size of the graphene powder is 50-70 μm, and the average number of layers is 3.

[0078] Example 4

[0079] The present embodiment provides a preparation method of a cellulose-based dispersant and a method for preparing large-sized graphene by aqueous phase exfoliation of the cellulose-based dispersant.

[0080] 1. Preparation of cellulose-based dispersants

[0081] In a reactor, 10 g of methyl cellulose with a molecular weight of 25,000 to 30,000 and 0.1 g of benzaldehyde are dissolved in 200 g of water to form a uniform solution, and then 0.5 g of nitric acid with a mass concentration of 0.2% is added. After the temperature is raised to 40°C, the reaction is carried out for 10 hours, and the benzaldehyde and cellulose undergo an aldol condensation reaction to generate a product, cellulose condensation benzaldehyde; then sodium hydroxide is added to neutralize the acid in the system until the pH of the system is neutral, and then 0.2 g of hydrogen peroxide is added to further oxidize the benzaldehyde that has not participated in the reaction into benzoic acid to remove the bitter almond taste, and after drying, a cellulose-based dispersant is obtained.

[0082] 2. Preparation of large-size graphene by aqueous phase exfoliation

[0083] 20 g of natural flake graphite (100 mesh), 3 g of a cellulose-based dispersant and 78 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 2500 rpm for 10 hours to obtain a graphene slurry.

[0084] The graphene slurry is spray-dried to obtain graphene powder. According to a particle size analyzer test, the lateral size of the graphene powder is 50-100 μm, and the average number of layers is 5.

[0085] Example 5

[0086] The present embodiment provides a preparation method of a cellulose-based dispersant and a method for preparing large-sized graphene by aqueous phase exfoliation of the cellulose-based dispersant.

[0087] 1. Preparation of cellulose-based dispersants

[0088] In a reactor, 10 g of hydroxypropyl methylcellulose with a molecular weight of 25,000 to 30,000 and 0.5 g of benzaldehyde are dissolved in 400 g of water to form a uniform solution, and then 0.5 g of acetic acid with a mass concentration of 2% is added. After the temperature is raised to 100° C., the mixture is reacted for 2 hours, and benzaldehyde and cellulose undergo an aldol condensation reaction to generate a product, cellulose condensation benzaldehyde; then sodium hydroxide is added to neutralize the acid in the system until the pH of the system is neutral, and then 1 g of hydrogen peroxide is added to further oxidize the benzaldehyde that has not participated in the reaction into benzoic acid to remove the bitter almond taste. After drying, a cellulose-based dispersant is obtained.

[0089] 2. Preparation of large-size graphene by aqueous phase exfoliation

[0090] 20 g of natural flake graphite (2 mesh), 5 g of a cellulose-based dispersant and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 1000 rpm for 25 hours to obtain a graphene slurry.

[0091] The graphene slurry is spray-dried to obtain graphene powder. According to a particle size analyzer test, the lateral size of the graphene powder is 100-300 μm, and the average number of layers is 5.

[0092] Comparative Example 1

[0093] This comparative example provides a method for preparing large-sized graphene by aqueous phase exfoliation, which adopts the same implementation as Example 1, except that no cellulose-based dispersant is added. Other process steps and parameter conditions are the same as those in Example 1.

[0094] The specific preparation method is as follows:

[0095] 20 g of natural flake graphite (32 mesh) and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 10 hours to obtain a slurry.

[0096] The slurry is spray-dried to obtain graphene powder, and the powder is tested by a particle size analyzer, which is graphite microsheets with a lateral size of less than 290 μm and an average number of 40 layers.

[0097] Comparative Example 2

[0098] This comparative example provides a method for preparing large-sized graphene by aqueous phase exfoliation, which adopts the same implementation as Example 1, except that the cellulose-based dispersant in Example 1 is replaced with hydroxyethyl cellulose of equal mass. The other process steps and parameter conditions are the same as those in Example 1.

[0099] The specific preparation method is as follows:

[0100] 20 g of natural flake graphite (32 mesh), 2 g of hydroxyethyl cellulose and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 10 hours to obtain a slurry.

[0101] The slurry is spray dried to obtain powder, and the powder is tested by a particle size analyzer, which shows that the powder is graphite microsheets with a lateral size of less than 240 μm and an average number of layers of 35 layers.

[0102] Comparative Example 3

[0103] This comparative example provides a method for preparing large-sized graphene by aqueous phase exfoliation, which adopts the same implementation as Example 1, except that the cellulose-based dispersant in Example 1 is replaced with an equal mass of sodium carboxymethyl cellulose. The other process steps and parameter conditions are the same as those in Example 1.

[0104] The specific preparation method is as follows:

[0105] 20 g of natural flake graphite (32 mesh), 2 g of sodium carboxymethyl cellulose and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 10 hours to obtain a slurry.

[0106] The slurry is spray dried to obtain powder, and the powder is tested by a particle size analyzer, which shows that the powder is graphite microsheets with a lateral size of less than 220 μm and an average number of layers of 30 layers.

[0107] Comparative Example 4

[0108] This comparative example provides a method for preparing large-sized graphene by aqueous phase exfoliation, which adopts the same implementation as Example 1, except that the cellulose-based dispersant in Example 1 is replaced by a mixture of hydroxyethyl cellulose and benzaldehyde.

[0109] The other process steps and parameter conditions are the same as those in Example 1.

[0110] The specific preparation method is as follows:

[0111] 20 g of natural flake graphite (32 mesh), 1.82 g of hydroxyethyl cellulose, 0.182 g of benzaldehyde and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 10 hours to obtain a slurry.

[0112] The slurry is spray dried to obtain powder, and the powder is tested by a particle size analyzer, which shows that the powder is graphite microsheets with a lateral size of less than 200 μm and an average number of layers of 28 layers.

[0113] Comparative Example 5

[0114] This comparative example provides a method for preparing large-sized graphene by aqueous phase exfoliation, which adopts the same implementation as Example 1, except that the cellulose-based dispersant in Example 1 is replaced with an equal mass of PVPK30. The other process steps and parameter conditions are the same as those in Example 1.

[0115] The specific preparation method is as follows:

[0116] 20 g of natural flake graphite (32 mesh), 2 g of polyvinylpyrrolidone PVPK30 and 75 g of deionized water were fully stirred and added into a sand mill at a sand milling speed of 3000 rpm for 10 hours to obtain a slurry.

[0117] The slurry is spray-dried to obtain powder, and the powder is tested by a particle size analyzer, which is graphite microsheets with a lateral size of less than 20 μm and an average number of layers of 20 layers.

[0118] Performance Testing

[0119] 1. The size, concentration and number of layers of the graphene or graphite microsheets prepared in Examples 1-5 and Comparative Examples 1-5 were characterized and tested respectively. The results are shown in Table 1.

[0120] Table 1 Graphene test results

[0121]

[0122]

[0123] 2. Take 20 mL of the slurry in the embodiment and the comparative example respectively, centrifuge them at 3000 rpm for 30 min, and observe the state of the slurry after centrifugation. The results are shown in Table 2.

[0124] Table 2 State changes of graphene slurry after centrifugation

[0125] sample Slurry changes Example 1 No stratification, mixed uniformly Example 2 No stratification, mixed uniformly Example 3 No stratification, mixed uniformly Example 4 No stratification, mixed uniformly Example 5 No stratification, mixed uniformly Comparative Example 1 Obvious stratification Comparative Example 2 Obvious stratification Comparative Example 3 Obvious stratification Comparative Example 4 Obvious stratification Comparative Example 5 Obvious stratification

[0126] It can be concluded from the test results of the embodiments and comparative examples in the present application that the cellulose-based dispersant prepared in the present application has a better exfoliation effect and a better stabilization effect on graphite than the dispersant in the comparative example. The cellulose-based dispersant in the present application can be used to produce large-size, high-concentration, high-quality and stable graphene.

[0127] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A cellulose-based dispersant, characterized in that The cellulose-based dispersant is an acetal compound generated by the reaction of cellulose and aromatic aldehyde; wherein the number average molecular weight of the cellulose is greater than 8000; Preferably, the number average molecular weight of the cellulose is ≥25000; Preferably, the number average molecular weight of the cellulose is 25000 to 30000; Preferably, the cellulose is water-soluble cellulose; Preferably, the water-soluble cellulose is at least one of hydroxyethyl cellulose, methyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose; Preferably, the aromatic aldehyde is one of benzaldehyde, phenylacetaldehyde, phenylpropionaldehyde, and 2-naphthaldehyde; Preferably, the aromatic aldehyde is benzaldehyde.

2. A method for preparing a cellulose-based dispersant as claimed in claim 1, characterized in that: The following steps are involved: The cellulose, aromatic aldehyde and water are fully mixed to form a uniform solution; Then, an acid is added thereto, the temperature is raised for reaction, the pH of the system is adjusted to 7, an oxidant is added, and the system is dried to obtain the cellulose-based dispersant; Preferably, the mass ratio of cellulose, aromatic aldehyde and water is 10:(0.1-1):(200-600); Preferably, the acid is at least one of hydrochloric acid, nitric acid, sulfuric acid and acetic acid; Preferably, the temperature of the reaction is 40 to 100° C., and the reaction time is 2 to 10 hours.

3. Use of the cellulose-based dispersant according to claim 1 or the cellulose-based dispersant prepared by the preparation method according to claim 2 in the preparation of large-sized graphene.

4. A method for preparing large-size graphene, characterized in that: The following steps are involved: After graphite, a cellulose-based dispersant and a solvent are uniformly mixed, they are mechanically exfoliated to obtain large-sized graphene; wherein the cellulose-based dispersant is the one described in claim 1 or is obtained by the preparation method described in claim 2.

5. The method for preparing large-size graphene according to claim 4, characterized in that: The size of the graphite is 2-100 meshes.

6. The method for preparing large-size graphene according to claim 4, characterized in that: The graphite is one of natural flake graphite and expanded graphite.

7. The method for preparing large-size graphene according to claim 4, characterized in that: The solvent is at least one of water, NMP and DMF; Preferably, the solvent is water.

8. The method for preparing large-size graphene according to claim 4, characterized in that: The mass ratio of the graphite, the cellulose-based dispersant and the solvent is 20:(2-5):(75-78).

9. The method for preparing large-size graphene according to claim 4, characterized in that: The mechanical stripping is carried out by sand grinding; Preferably, the sand milling speed is 1000-3000 rpm, and the time is 5-25 hours.

10. The method for preparing large-size graphene according to any one of claims 4 to 9, characterized in that: The lateral size of the graphene is 50 to 300 μm, and the average number of layers is less than 5.